Lack of substantial improvements in the landscape of alcohol-related hepatocellular carcinoma in the last 15 years: The need to improve cancer prevention and surveillance. (March 2023) - Reggidori, N.; Bucci, L.; Santi, V.; Stefanini, B.; Lani, L.; Rampoldi, D.; Caturelli, E.; Farinati, F.; Masotto, A.; Stefanini, B.; Mega, A.; Biasini, E.; et al.
Abstract : Introduction: Alcohol abuse and metabolic disorders are leading causes of hepatocellular carcinoma (HCC) worldwide. Alcoholic aetiology associates with a worse prognosis compared to hepatitis B and C infections, due to a lower percentage of HCCs diagnosed under regular surveillance and a higher comorbidity burden in alcoholic patients. Aim: This study aimed at describing the evolving clinical scenario of alcohol-related HCC over a 15-year period (2006-2020) in Italy. Material and Methods: Data of the Italian Liver Cancer (ITA.LI.CA) registry were used: 1391 alcoholic patients were allocated to 3 groups based on the year of cancer diagnosis (2006-2010; 2011-2015; 2016-2020) and patient characteristics, HCC treatment and overall survival were compared among groups. Survival predictors were also investigated. Results: Around 80% of alcoholic patients were classified as metabolic dysfunction-associated fatty liver disease (MAFLD) cases. Throughout the quinquennia, <50% of HCCs were detected by surveillance programs. The tumour burden at diagnosis slightly decreased but not enough to change the distribution of ITA.LI.CA cancer stages. The use of intra-arterial and targeting systemic therapies increased across quinquennia. A modest improvement of survival was observed in the last quinquennia, particularly after 24 months of patient observation. Cancer stage, HCC treatment and presence of oesophageal varices were independent predictors of survival. Conclusion: In the last 15 years, minor improvements have been obtained in the outcome of alcohol-related HCC, mainly because of a persistent underuse of surveillance programs and the consequent steadily low amenability to curative treatments. Oesophageal varices are an independent grim prognosticator and therefore this variable should be included in prognostic systems. MAFLD is a widespread condition in alcohol abusers, but its presence did not achieve a pivotal prognostic role once HCC has developed.